Development of Collaborative Learning Devices on Two-Dimentional Figure Topic of Mathematics for 4th Students - Ni Komang Supitri Pebriari; I Gede Margunayasa; Ni Nyoman Kusmariyatni (Universitas Muhammadiyah Prof. Dr. HAMKA Press, 2019)
This study aimed to develop collaborative learning device for mathematic course specified on two-dimentional figure on 4th grade students. The design of this study was Research and Development by using Prototype model in which the steps were 1) listening and obtaining the need for the device 2) organizing and making prototype 3) testing. The subject of this study was a collaborative learning device. Instrument used to measure the validity of the learning device was rating scale in the form of assessment tools from the expert. The data were obtained by using methods, namely questionnaire by using quantitative and qualitative data analysis. Testing resulted the numeric data and the average score was converted in PAP table 5 scale. The result showed that 1) collaborative learning device in mathematic course specified on two-dimentional figure involved 1 syllabus, 6 lesson plans, 6 student worksheet, 2) this product was validated by expert of mathematic, expert in education and 2 teachers from different school with the average score 4.42 for syllabus, 4.51 for lesson plan and 4.62 for student worksheet and the category was “very good”.